y=-2E+05ln(x)+1E+06

Simple and best practice solution for y=-2E+05ln(x)+1E+06 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=-2E+05ln(x)+1E+06 equation:


Simplifying
y = -2E + 5ln(x) + 1E + 6

Multiply ln * x
y = -2E + 5lnx + 1E + 6

Reorder the terms:
y = 6 + -2E + 1E + 5lnx

Combine like terms: -2E + 1E = -1E
y = 6 + -1E + 5lnx

Solving
y = 6 + -1E + 5lnx

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = 6 + -1E + 5lnx

See similar equations:

| -6--2x/-4 | | 0x+1y=3 | | x=3y^3+4y | | 4.5(r+1)=27-4.5 | | 3m+2n=2 | | Y=-0.5x-3 | | Cos(x+50)=-0.7 | | 3n+8-4n=-17 | | 2x-6x=1-3 | | 13x+29=-10+39x | | x^2+y^2+6xy+10=0 | | k-11=60 | | z/2−6≤−2 | | (3+1)(2x-5)= | | (2x+4)(x-6)= | | x-2=-27 | | -22=6(2(-5.33)+7) | | 3x+8y-6z=24 | | 2x=20+20 | | k/-3-11 | | -5n+8=-07 | | 6(2(5.33)+7)= | | F(x)=7x^3 | | 4(2x-5)=120 | | -49x^2=-64 | | y=0.0002x^3-0.04x^2+2x | | 4x-26=3x | | 2w+1l= | | -22=6(2k+7) | | 50-80+30=-60 | | n^2-n-93=0 | | u=135+396 |

Equations solver categories